Էջեր Երևանի երաժշտական ստուդիայի պատմությունից - Նաիրա Մադոյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена истории Ереванской музыкальной студии, которая открылась 22 декабря 1921 г., действовала 2 года под руководством Романоса Меликяна и 1 октября 1923 г. стала основой для первого и единственного в армянской действительности высшего музыкального учебного заведения – Ереванской государственной консерватории.This article is dedicated to the history of Yerevan music studio. Its official opening took place on the 22nd of December of 1921 and the studios’ principal for two years was Romanos Melikian. On the first of October in 1923 the studio came to be a base for the foundation of the first and sole higher musical educational establishment, Yerevan Komitas State Conservatory.
Keywords: MT Musical instruction and study